2014
DOI: 10.1093/ageing/aft210
|View full text |Cite
|
Sign up to set email alerts
|

Macular pigment optical density is related to cognitive function in older people

Abstract: MPOD is related to cognitive function in older people. Its role as a potential biomarker of cognitive function deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 17 publications
9
104
2
2
Order By: Relevance
“…For example, Nolan et al (36) found that supplementing patients with AD with macular carotenoids did not improve cognitive function. Studies that focused on older adults at risk of, but with no signs of, dementia found consistent relations between cognitive function and LZ status (37)(38)(39)(40)(41)(42). Of course, for the result to be valid even for this highly selective sample, the measures of cognitive function and decline must also be valid.…”
Section: Study Populationmentioning
confidence: 95%
“…For example, Nolan et al (36) found that supplementing patients with AD with macular carotenoids did not improve cognitive function. Studies that focused on older adults at risk of, but with no signs of, dementia found consistent relations between cognitive function and LZ status (37)(38)(39)(40)(41)(42). Of course, for the result to be valid even for this highly selective sample, the measures of cognitive function and decline must also be valid.…”
Section: Study Populationmentioning
confidence: 95%
“…Individuals with lower MPOD also had poorer prospective memory, took longer time to complete a trail-making task, and had slower and more variable reaction times on a choice reaction time task (Feeney et al, 2013). MPOD levels were significantly associated with better global cognition, verbal learning and fluency, recall, processing speed and perceptual speed in older adults from the age-related maculopathy ancillary study of the Health Aging and Body Composition Study (Vishwanathan et al, 2014a). Finally, in subjects with mild cognitive impairment, MPOD was related to cognition including the composite score on the mini-mental state examination, visual-spatial and constructional abilities, language ability, attention, and the total scale on the repeatable battery for the assessment of neuropsychological status .…”
Section: Lutein and Zeaxanthin: The Function In The Brainmentioning
confidence: 98%
“…In adults, higher lutein status is related to better cognitive performance, and lutein supplementation improves cognition. [108] A study was conducted on 35 community dwelling older adults ages 65-94 engaged in an fMRI adapted verbal paired associates (VPA) task, including a learning and recalling test. Lutein/zeaxanthin levels were estimated using a standard Macular Pigment Ocular Density (MPOD) procedure and used as a covariate in the fMRI analyses.…”
Section: Skin Healthmentioning
confidence: 99%